Reimagining Legal Pluralism in Africa : Balancing Indigenous, State, and Religious Laws - Diala, Anthony C.,; Rautenbach, Christa, (Developments in International Law ;, 2024)
This collection challenges the prevailing conflict of laws approach to the interaction of state and indigenous legal systems. It introduces adaptive legal pluralism as an alternative framework that emphasises dialogue and engagement between these legal systems. By exploring a dialogic approach to legal pluralism, the authors shed light on how it can effectively address the challenges stemming from the colonial imposition of industrial legal systems on Africa's agrarian political economies.